Plan de negocios para la creación de una empresa dedicada al ensamblaje y comercialización de calefones híbridos en la ciudad de Quito - Álava Loza, Daniela Alexandra (2016)
The present business plan will demonstrate the viability of the creation of a company dedicated to the assembly and commercialization of hybrid water-heating systems in Quito in a 5 year horizon. The brand, BRÍO, is developed both for the company and its products, which will be referred to as electro-solar hybrid systems. The target of BRÍO are the consumers of the higher stratum, in ages between 33 and 59 years old, residing in single-family houses of 3 to 5 members and an environmental consciousness. By using national raw material and hand labour to elaborate the structure of its systems, importing the technological components of Mexico, Germany and the Unites states, leaders in the development of solar energy, and offering 100% customized products, BRÍO bases its competitive advantage in the ecological factor, its community commitment and the customization of its products. The present business proves to be profitable, both for the project and for the investor.